2021
DOI: 10.1016/j.artd.2021.08.016
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical and Anatomical Alignment Guide Techniques Are Superior to Freehand in Achieving Target Orientation of an Acetabular Component

Abstract: Background: Achieving accurate and consistent acetabular component orientation remains a major challenge in total hip arthroplasty. Methods: We used a pelvic model to compare freehand techniques vs mechanical and anatomical alignment guides in achieving a target operative inclination (OI) and operative anteversion (OA). Thirty subjects comprising consultant orthopedic surgeons, orthopedic trainees, and nonsurgical staff positioned an acetabular component in a pelvic model using 3 different methods for guiding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 35 publications
(58 reference statements)
0
5
0
Order By: Relevance
“…Using an inclinometer instead of mechanical guides may be more accurate. While some studies found superior results compared to freehand positioning and traditional mechanical guides, especially regarding achieving the targeted inclination and reducing outliers, other studies found no differences [ 54 , 71 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Using an inclinometer instead of mechanical guides may be more accurate. While some studies found superior results compared to freehand positioning and traditional mechanical guides, especially regarding achieving the targeted inclination and reducing outliers, other studies found no differences [ 54 , 71 ].…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, a spirit level instead of a simple rod can be used. These methods showed superior results to freehand positioning [ 54 ].…”
Section: Cup Positioning Techniquesmentioning
confidence: 99%
“…Additionally, inconsistencies in the size and shape of the operating room may alter the surgeon's perception of patient orientation [90]. Therefore an alignment rod attached to the insertion handle of the cup has proven to be more accurate in comparison to free hand cup placement [91]. This rod allows the surgeon to more appropriately align the guide to visualize anteversion and inclination based on the floor and longitudinal axis of the patient.…”
Section: Acetabular Componentmentioning
confidence: 99%
“…These methods are of limited guidance value in the operation. With respect to the anteversion of the acetabular cup, many scholars believed that satisfactory anteversion could be obtain when the inferior edge of the acetabular cup was placed parallel to the transverse acetabular ligament 5 7 . However, not all of the transverse acetabular ligament could be separated in the operation, especially Beverland grade four 8 .…”
Section: Introductionmentioning
confidence: 99%